Neoadjuvant vs. adjuvant chemotherapy for cholangiocarcinoma: A propensity score matched analysis. Issue 8 (August 2019) - Yadav, Siddhartha; Xie, Hao; Bin-Riaz, Irbaz; Sharma, Prabin; Durani, Urshila; Goyal, Gaurav; Borah, Bijan; Borad, Mitesh J.; Smoot, Rory L.; Roberts, Lewis R.; Go, Ronald S.; McWilliams, Robert R.; et al.
Abstract: Background: Chemotherapy is frequently used in cholangiocarcinoma as an adjunct to surgical resection, but the appropriate sequence of chemotherapy with surgery is unclear. Patients and methods: Using the National Cancer Database, we identified patients who underwent surgery and chemotherapy for stage I-III cholangiocarcinoma between 2006 and 2014. The propensity score reflecting the probability of receiving neoadjuvant chemotherapy was estimated by multivariate logistic regression method. Patients in the neoadjuvant and adjuvant chemotherapy study arms were then propensity-matched in 1:3 ratios using the nearest neighbor method. Overall Survival (OS) in the matched data set was estimated using the Kaplan-Meier method. Hazard ratios (HRs) were calculated using Cox proportional hazard regression model. Results: Of the 1450 patients who met our inclusion criteria, 299 (20.6%) received neoadjuvant chemotherapy while 1151 (79.3%) received adjuvant chemotherapy. The median age at diagnosis was 63 years. 278 patients in the neoadjuvant group were matched to 700 patients in the adjuvant group. In the matched cohort, patients who received neoadjuvant chemotherapy had a superior OS compared to those who received adjuvant chemotherapy (Median OS: 40.3 vs. 32.8 months; HR: 0.78; 95% CI: 0.64–0.94, p = 0.01). The 1- and 5-year OS rates for the neoadjuvant chemotherapy group were 85.8% and 42.5% respectively compared to 84.6% and 31.7% for the adjuvant chemotherapy group. Conclusion: In this large national database study, neoadjuvant chemotherapy was associated with a longer OS in a select group of patients with cholangiocarcinoma compared to those who underwent upfront surgical resection followed by adjuvant chemotherapy.